THE EFFECT OF FERTILIZATION PHYSICAL TEXTURES AND DOSAGES OF GOAT MANURE FERTILIZER ON PLANT GROWTH AND YIELD OF DWARF ELEPHANT GRASS (Pennisetum purpureum cv. Mott) - K. A., Manalu; Witariadi, N. M.; Kusumawati, N. N. C. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aimed to determine the effect and interaction between physical texture and different dosage of goat manure fertilizer on plant growth and yield of pennisetum purpureum cv. Mott. The research was conducted at the Glasshouse, Sesetan Research Station, Faculty of Animal Husbandry, Udayana University at Jalan Raya Sesetan, Denpasar. The study was conducted for 12 weeks, using a completely randomized design (CDR) with factorial pattern. The first factor was small oval shaped (BB), refined texturcy (BH). The second factor was levels dosages of goat manure: 0 tonnes  ha -1 (D0), 10 tonness ha -1 (D2), 20 tonnes ha -1 (D2), and 30 tonness ha -1 (D3). There were eight treatment and each treatment was repeated four times, so there were 32 unit experimental units. Variables measured in this experiment were growth, yield, and plant growth characteristic variabels. The result showed that there was an interaction between physical textures and dosage of goat manure on height of grass, weight of dry leaf, weight of dry roots, total weight dry grass. The refined texture showed better result than the small shaped pellet. The best dosage of goat manure for growth and yield of Pennisetum purpureum cv. Mott was observed on 30 tonnes ha -1 . Based on above results, it is concluded that Pennisetum purpureum cv. Mott response the best during refined type at 30 tons ha -1 goat manure fertilizer.